Development of glomerular filtration rate monitor based on creatinine kinetic modelling in critically ill patients - Md Ralib, Azrina; Mat Nor, Mohd Basri; Mohamed, Rozilah @ Abdul Hadi; Abdullah, Norzamzila; Jamaludin, Ummu Kulthum; Dzaharudin, Fatimah (2018)
Background: Creatinine kinetic denotes that under steady state, creatinine production (G) equals to creatinine excretion rate (E), and if production exceeds excretion, GFR is impaired. Kinetic estimate of GFR (keGFR) offers a more accurate estimate of GFR in the acute settings with rapidly changing kidney functions. Objectives: We evaluated keGFR and E/eG ratio in diagnosis of AKI and its recovery. We also compared their diagnostic ability to the plasma Cystatin C and NGAL. Methods: This was a prospective observational study of critically ill patients. Inclusion criteria were patients >18 years old with sepsis and procalcitonin>0.5ng/ml. Results: 70 patients were recruited. keGFR had the least bias with the mean differences nearest to zero (-18 ml/min) when compared to CrCl. keGFRCr and keGFRCysC were strongly diagnostic of AKI with AUC of 0.93 (0.87 to 0.99). In 39 patients with AKI, 15 recovered within 3 days. In these cases, E/eG ratio strongly predicted AKI recovery (AUC 0.83 (0.69 to 0.97)). The AUC of plasma NGAL were highest for AKI diagnosed by keGFR on Day 1 and Day 2, and by E/eG ratio on Day 3. Conclusions: In critically ill patients with sepsis, keGFRCr and keGFRCysC had the least bias and fair precision when compared to CrCl. They diagnosed AKI with cut-off points of 77 and 86 ml/min respectively. E/eG ratio was useful for prediction of recovery in patients with AKI. NGAL best diagnosed AKI by keGFR and E/eG ratio.